2016
DOI: 10.4103/0970-9290.186241
|View full text |Cite
|
Sign up to set email alerts
|

Using smartphone video “selfies” to monitor change in toothbrushing behavior after a brief intervention: A pilot study

Abstract: Background Attempts to refine toothbrushing (TB) technique, an ingrained habit in adults, can meet with some challenges. Recently, the role of proactive interference as a barrier to improving the learning of proper brushing has been proposed. This pilot feasibility study was designed to investigate TB behavior and to see how it changes after training. Smartphone video “selfies” (SPVSs) are increasingly being used in the medical field to assess, monitor, and determine the progression of diseases. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
(47 reference statements)
0
4
0
2
Order By: Relevance
“…A 2018 study used toothbrushes that were connected to a smartphone application in order to track brushing habits such as frequency, duration, and surface coverage . More advanced systems such as 3‐D motion tracking devices and “selfie” tooth brushing video interventions have also been tested in pilot studies in order to provide an even more detailed analysis of tooth brushing technique . Currently, the implementation of this data collection method is still in its relative infancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2018 study used toothbrushes that were connected to a smartphone application in order to track brushing habits such as frequency, duration, and surface coverage . More advanced systems such as 3‐D motion tracking devices and “selfie” tooth brushing video interventions have also been tested in pilot studies in order to provide an even more detailed analysis of tooth brushing technique . Currently, the implementation of this data collection method is still in its relative infancy.…”
Section: Discussionmentioning
confidence: 99%
“…order to provide an even more detailed analysis of tooth brushing technique. 57,58 Currently, the implementation of this data collection method is still in its relative infancy. As these types of technology develop and gain widespread adoption, these data can be analyzed to provide immediate feedback to patients.…”
Section: Where To Gather Datamentioning
confidence: 99%
“…One of the most important behaviors in oral hygiene care change techniques is user interaction with the app [ 96 ]. Our results showed that one app included learning of oral self-care with virtual model teeth and enabled the user to perform self-based oral health care interaction in the app.…”
Section: Discussionmentioning
confidence: 99%
“…Diversas formas de comunicação e interação mais atuais estão sendo utilizadas para melhorar a precisão e a qualidade da higiene bucal (Madan Kumar et al, 2016).…”
Section: Capítulo I: Introduçãounclassified
“…Madan Kumar et al (2016) observaram viabilidade de mudança de comportamento na higiene bucal, utilizando a câmera do smartphone na forma de selfies. Também em 2016, Kasai et al, utilizaram câmeras comerciais e intraorais para estabelecer um método alternativo para calcular a quantidade de placa além de estimar o índice de placa utilizando unicamente a imagem dos dentes anteriores.…”
Section: Capítulo I: Introduçãounclassified